Confirmación molecular de caso clínico diagnosticado en 1984 con atrofia muscular espinal tipo II (AME tipo II) y análisis familiar de portadores - Ousset, María Julia (2022)
Spinal muscular atrophy (SMA) is a neurodegenerative disease considered one of the most common and most devastating ?rare? diseases known, and one of the main inherited causes of infant mortality. It has an approximate incidence of 1/6000 to 1/10000 births, and a carrier frequency of 1/40 -1/60 in the general population. The gene that has been associated as a determinant of the disease is called SMN1 and codes for the SMN protein. This disease most affects the cells of the anterior horn of the spinal cord (motor neurons) and causes symmetric proximal weakness and progressive atrophy of muscle groups. The disease is classified into 4 groups according to the clinical picture based on the severity of the symptoms, the age of onset and its evolution.\nThe disease phenotypes range from severe neonatal manifestation to adult form with minimal weakness. The severity of the disease has been correlated with the number of copies of the SMN2 gene, a sequence homologous to SMN1, whose coding sequence differs by one nucleotide in exon 7 (c.840C> T), respect to SMN1. Both, SMN1 and SMN2, consist of nine exons that code for the 294 amino acid SMN protein. The SMN2 gene, unlike SMN1, produces only 10-25% active SMN protein. Currently, clinical research studies are being carried out with drugs that stimulate a greater synthesis of active protein from SMN2, these therapies range from antisense oligo therapies (Spinraza) to gene therapy (Zolgensma).\nThe most widely methodologies used for the molecular diagnosis of the disease are PCR-RFLP (restriction fragment length polymorphism), sequencing and MLPA (multiplex ligation dependent probe amplification) and for genotype-phenotype correlation studies, quantitative molecular techniques are used that allow performing gene dosing of SMN2 as real-time PCR or MLPA. Carriers of the disease can be identified by indirect methods by performing linkage analysis, or by the aforementioned quantitative methodologies.\nIn 2007 the Senate and the Chamber of Deputies of the Province of Buenos Aires passed a law (Law 13682) that declares the investigation and treatment of AME of provincial interest. In addition, this initiative establishes that the Executive Branch, through the Ministry of Health, implement specific programs aimed at disseminating the characteristics of the disease, promotes\nknowledge of its antecedents and effects, its methods of diagnosis and detection, informing about currently existing treatments and organizing regional health responses for patients affected by the disease. This information supports the need in the country for statistics and information on patients and carriers in the population and adequate genetic counseling for families with affected people to better understand the probabilities and risks of disease in their offspring.\nThe aim of this project was to study and confirm the clinical diagnosis of SMA in a patient using molecular techniques, and to identify carriers in the family. This was one of the first cases clinically diagnosed with SMA in Argentina in 1984, when not even the determining gene for the disease was yet known. During the development of this work, by means of different techniques, the SMA diagnosis of the patient was confirmed and two carriers were identified among their relatives. In contrast to what has been reported in gene dosing by real-time PCR for SMA, in this work the technique was developed with two reference genes instead of one. This minimizes false results due to polymorphisms in the primer binding sequences and gives a higher degree of certainty to the result obtained.